CHARACTERISTIC OF HACAU DIM SUM FELL QUALITY WHICH WAS FORTIFIED WITH DIFFERENT SEAWEED (Eucheuma sp) FLOUR - Rafika Apriany; N Ira Sari; Dahlia ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
ABSTRACTThe research was intended to evaluate the characteristic of hakau dim sum fell quality witch was fortified with seaweed flour. 10 kg of seaweed was obtained from one of market in pekanbaru was processed to seaweed flour. Hacau dim sum fell was made from tang mine flour, wheat flour, egg, cooking oil, hot water and it was fortified with 0g, 30g, 50g, and 70g of seaweed. Then, for making the contain of dim sum; shrimp, pepper, sugar and salt were prepared. Parameter of this research was observed to folding test, organoleptic, and proximat analysis. The result showed that the fell of hacau dim sum which was fortified with 70g of seaweed flour (R3) was the best treatment with folding test AA, organoleptic value in appearance 8.33, odor 8.33, flavor 3.00, texture 8.33, for moisture content 56.29%, protein content 24.71%, lipid content 9.24%, ash content 2.04% and crude fiber 1.82%.Keywords: Dim sum fell, Hacau, Seaweed